The Peruvian petroleum industry: Analysis of contract and tax systems - Anke Meyer (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1986)
The main features of the Peruvian petroleum sector are described with special reference to the development of the institutional regulation of the industry since the early sixties. An econometric model has been developed to study the determinants of historical investment and production patterns of foreign, mainly U.S. oil companies. This model seems to capture one of the main characteristics of crude oil operations. Given the field size, there exists an optimal, technically determined production profile which mainly determines production and investment levels. A detailed analysis of various tax systems was performed with a simulation model based on Peruvian geological and cost conditions. Here, a variation of the resource rent tax seems to be a compromise between too generous tax systems and tax systems that introduce major disincentives to reserve development in high cost areas.
Keywords: 330; Mineralölwirtschaft; Mineralölsteuer; Peru; Mineralölwirtschaft